How to Understand Disorderly Boys - An Exchange of Didactic Experiences Among Textile-Sloyd Teachers in an Internet-based Community of Practice - Samuelsson, Marcus (FormAkademisk, 2015)
This paper reports on a case study in which a textile-sloyd teacher sent a message to an internet-based community of practice seeking advice from other textile-sloyd teachers regarding how to cope with unruly boys. Two major themes emerged from a interview and the discussion on the Internet: 1) behaviour analysis and 2) coping attempts The analysis also revealed two themes related to the exchange of experiences: 1) descriptions of the problem as pertaining to the pupils, the process, classroom management, freedom of choice, or connection to everyday life and 2) suggested solutions, such as area of activity, competences, leadership and techniques. The article concludes with a discussion demonstrating that the collegial exchange about disorderly boys appears to have strengthened and challenged this internet-based community of practice.